Measurement and predictors of the financial performance of public health enterprises in Italy - Peter PERGER; Achim HECKER (Journal of Health and Social Sciences)
Introduction: In the healthcare sector, hospitals are by far the largest producers. As their costs continue to rise, sustaining long-term financial sustainability is becoming increasingly difficult. The measurement of healthcare providers’ financial performance is less developed in European countries compared to others; structured information on financial performance is especially scarce when providers are publicly financed. Methods: This study constructs and validates a multidimensional financial performance measure (common factor approach) by the example of Public Health Enterprises (PHEs) in Italy, based on publicly available data. In a second step, several predictor variables are examined in a PLS-SEM model (partial least squares - structural equation model), including the environmental factor umbrella institutions' financial performance (Region), structural factors size (absolute), size class, teaching/scientific function and specialization, operational factor occupancy and complexity of treatment and the staffing factor non-medical staff rate. Results: The proposed measure aggregates multiple dimensions of financial performance (e.g. profitability, liquidity, capital structure) and satisfies all necessary conditions of construct reliability and validity. For PHEs in Italy, financial performance is significantly negatively influenced by the Region's financial performance (financial recovery plans) and the complexity of treatment, whereas medium-sized and specialized providers show comparatively significantly better performance levels. For the variables: size (absolute), teaching/scientific function, occupancy, and non-medical staff rate, no significant influence could be found. Discussion: This study provides insights into the financial performance of PHEs and is useful in identifying risks (negative influencing predictors and their trend) as well as favorable circumstances (positive influencing predictors and their trend). Moreover, different policymakers (the central government, the central bank, regions, and supervisory bodies, such as the court of auditors) may take an advantage from using this information and methodology to ensure the healthcare system is sustainable and adequately controlled in the long run. Our approach may also be useful for banks and credit institutions, or hospital pharmaceutical and medical device suppliers in estimating financial risks associated with their counterparty.